Evaluation on the implementation of Bachelor of Education program, Faculty of Sport Science and Coaching - Jani Julismah, Mohd Shariff Abdul Rahim, Salimin Norkhalid, Shahril Mohd Izwan, Mohd Rasyid Nelfianty, Jusoh Normah, Low Jeffrey, Fook Lee, Elumalai G (Universiti Pendidikan Sultan Idris, 2016)
Evaluation on the implementation of Bachelor of Education program, Faculty of Sport Science and Coaching by Jani Julismah, Mohd Shariff Abdul Rahim, Salimin Norkhalid, Shahril Mohd Izwan, Mohd Rasyid Nelfianty, Jusoh Normah, Low Jeffrey, Fook Lee, Elumalai G